Algal natural products in relation to the State of Hawaii's seaweed populations. - Santos, Gertrudes; Doty, Maxwell S. (Hawaii University of Hawaii, 1985)
Hawaii Botanical Sciences Paper no.43
Keywords: Natural products--Hawaii.; Algal natural products--Hawaii.